A rare earth-vanadium liquid flow battery
By adding rare earth ions and stabilizers to the positive and negative electrode electrolytes of vanadium flow batteries, the problem of electrolyte instability caused by pentavalent vanadium ion polymerization is solved, and the electrochemical performance and stability of the battery are significantly improved.
Patent Information
- Application Number
- CN202411526644.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-10-30
AI Technical Summary
The polymerization of pentavalent vanadium ions in vanadium flow batteries leads to instability of the electrolyte, affecting the performance of the battery.
The rare earth ions and stabilizer 2-amino-4-hydroxybenzamide and methylsulfonic acid are added to the positive and negative electrode electrolytes to prevent the precipitation of pentavalent vanadium ions through complexation and adsorption, and the stability of the electrolyte is improved.
It significantly improves the electrochemical performance and stability of the electrolyte, extends the service life of the battery, and improves the charge and discharge performance.
Smart Images

Figure IGYWEGP24RNUUXFDAXNNUUJHCURJZXEVVQB1UZ7B 
Figure UPWSNRIIHXUL25CP1NLKEJTA80FFVJ7XA86F5ZCS 
Figure XQNUANOJ6YCE7B8G4C0RKR6ZKRG9WS6R3NGKKT3R
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of liquid flow batteries, and more specifically, to a rare earth-vanadium liquid flow battery. Background Art
[0002] Vanadium flow batteries have become one of the most promising methods for large-scale energy storage such as wind energy, solar energy and electricity peak shaving and valley filling due to their high energy conversion efficiency, long service life, adjustable capacity according to user requirements, high safety and environmental friendliness. Vanadium flow batteries are usually composed of electrolytes, electrodes, storage tanks, etc. There are many factors that affect their performance, but the performance of the electrolyte has the most obvious impact. As vanadium flow batteries are increasingly developing towards large scale and large capacity, the electrolyte is also developing towards high concentration. However, when the concentration of pentavalent vanadium ions in the positive electrode electrolyte is high, the self-polymerization of pentavalent vanadium ions can easily lead to crystallization, affecting the stability of the electrolyte. Therefore, adding some additives that can prevent the self-polymerization of pentavalent vanadium ions can effectively improve the stability of the positive electrode electrolyte.
[0003] At present, in order to inhibit the precipitation of pentavalent vanadium, people usually add inorganic or organic additives to the electrolyte. Commonly used inorganic additives include alkali metal salts such as oxalates, sulfates, and phosphates. Organic additives include urea, fructose, mannitol, methanesulfonic acid and aminomethylsulfonic acid, trifluoroacetic acid, polyacrylic acid, oxalic acid, methacrylic acid, citric acid, ethylenediaminetetraacetic acid (EDTA) and other organic acids.
[0004] The proper addition of additives can not only improve the stability of the electrolyte and effectively prevent VO(OH)3 from hydrolyzing to form V2O5 precipitation, but also improve the conductivity and electrochemical activity of the electrolyte. However, the addition of these additives will introduce some impurity elements, some of which will change the acidity of the system, which may increase the corrosion ability of the electrolyte and affect the overall service life of the battery stack. Summary of the invention
[0005] In order to solve the above technical problems, the present application provides a rare earth-vanadium liquid flow battery, which can significantly improve the electrochemical performance and stability of the electrolyte by adding rare earth ions to the positive and negative electrode electrolytes. At the same time, by adding stabilizers, the stability of the electrolyte can be further improved, and the battery charging and discharging performance can be improved.
[0006] The present application also provides a method for preparing positive and negative electrodes, specifically using ammonium polyphosphate to intercalate MXene, and then using the treated MXene to graft modify graphite felt. The obtained graphite felt electrode has good electrochemical activity and can further improve the electrochemical performance of the vanadium liquid flow battery.
[0007] The present application provides a rare earth-vanadium liquid flow battery, which adopts the following technical solution:
[0008] A rare earth-vanadium liquid flow battery, which consists of a negative circulation loop, a positive circulation loop, and a diaphragm located between the negative circulation loop and the positive circulation loop;
[0009] The negative circulation loop comprises a negative electrode chamber, a negative electrode electrolyte peristaltic pump, and a negative electrode liquid storage tank, wherein the negative electrode chamber, the negative electrode electrolyte peristaltic pump, and the negative electrode liquid storage tank are sequentially connected by a pipeline, and the negative electrode liquid storage tank is provided with a negative electrode electrolyte, and the negative electrode electrolyte circulates in the negative circulation loop;
[0010] The positive circulation loop comprises a positive electrode chamber, a positive electrode electrolyte peristaltic pump, and a positive electrode liquid storage tank, wherein the positive electrode chamber, the positive electrode electrolyte peristaltic pump, and the positive electrode liquid storage tank are sequentially connected by a pipeline, and a positive electrode electrolyte is provided in the positive electrode liquid storage tank, and the positive electrode electrolyte circulates in the positive circulation loop;
[0011] A negative electrode is arranged in the negative electrode chamber, a positive electrode is arranged in the positive electrode chamber, and the negative electrode chamber and the positive electrode chamber are separated by a diaphragm;
[0012] The negative electrode electrolyte is composed of V 2+ / V 3+ , rare earth ions, acid solution and stabilizer;
[0013] The positive electrode electrolyte is composed of VO2 + / VO 2+ , rare earth ions, acid solution and stabilizer;
[0014] The stabilizer consists of 2-amino-4-hydroxybenzamide and methanesulfonic acid.
[0015] Furthermore, the concentration of the stabilizer is 0.01-0.3 mol / L.
[0016] Preferably, the concentration of the stabilizer is 0.1 mol / L.
[0017] Furthermore, the molar ratio of 2-amino-4-hydroxybenzamide to methanesulfonic acid is 1:(0.01-0.2).
[0018] Furthermore, the concentration of the rare earth ions is 0.01-3 mol / L.
[0019] Furthermore, the rare earth is selected from at least one of scandium, yttrium, lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium and lutetium.
[0020] Furthermore, the acid solution concentration is 0.01-10 mol / L.
[0021] Preferably, the acid solution concentration is 1-6 mol / L.
[0022] Furthermore, the acid solution is selected from at least one of hydrochloric acid, sulfuric acid, acetic acid, and trifluoroacetic acid.
[0023] Furthermore, the V 2+ / V 3+ The concentration is 0.01-10mol / L.
[0024] Furthermore, the VO2 + / VO 2+ The concentration is 0.01-10mol / L.
[0025] Furthermore, the positive electrode and the negative electrode are selected from at least one of graphite felt, modified graphite felt, carbon felt and carbon cloth.
[0026] Preferably, the positive electrode and the negative electrode are made of modified graphite felt.
[0027] Furthermore, the modified graphite felt is prepared by the following preparation method:
[0028] The MAX phase compound is etched with a sodium hydroxide solution, and MXene powder is obtained after drying. The MXene powder is placed in an ammonium polyphosphate aqueous solution, stirred and mixed, and the upper clear liquid is taken by centrifugation to obtain a MXene modifier; graphite felt is placed in the MXene modifier, heated for reaction, and the graphite felt is washed after the reaction is completed, and the modified graphite felt is obtained after drying.
[0029] Furthermore, the MAX phase compound is one of Ti3AlC2, Ti2AlC, Nb2AlC, Nb4AlC3, V2AlC and Mo2AlC.
[0030] Furthermore, the concentration of the sodium hydroxide solution is 2-10 mol / L.
[0031] Furthermore, the mass fraction of the ammonium polyphosphate aqueous solution is 30-60wt.%.
[0032] Furthermore, the membrane is selected from one of a perfluorosulfonic acid resin-based proton exchange membrane, a polybenzimidazole proton exchange membrane, a sulfonated polyetheretherketone membrane, and a sulfonated polyimide membrane.
[0033] Furthermore, the method for preparing the negative electrode electrolyte comprises the following steps:
[0034] Will contain V 2+ / V 3+ The compound and the compound containing rare earth ions are added to water, stirred to dissolve, then the acid solution is added, stirred evenly, and finally the stabilizer is added, stirred evenly, and water is added to adjust the concentration of each component to obtain the product.
[0035] Furthermore, the preparation method of the positive electrode electrolyte comprises the following steps:
[0036] Will include VO2 + / VO 2+ The compound and the compound containing rare earth ions are added to water, stirred to dissolve, then the acid solution is added, stirred evenly, and finally the stabilizer is added, stirred evenly, and water is added to adjust the concentration of each component to obtain the product.
[0037] In summary, this application has the following beneficial effects:
[0038] (1) The present application can significantly improve the electrochemical performance and stability of the electrolyte by adding rare earth ions to the positive and negative electrode electrolytes. At the same time, by adding stabilizers, the stability of the electrolyte can be further improved, and the battery charging and discharging performance can be improved;
[0039] (2) The amino group and sulfonate group contained in the additive used in the present application can synergistically complex with the vanadium ions in the electrolyte. At the same time, the hydroxyl group in 2-amino-4-hydroxybenzamide is more active due to the effect of the benzene ring and is easy to adsorb the vanadium ions in the electrolyte, thereby effectively preventing V 5+ The precipitation significantly improves the stability of the electrolyte. In addition, the addition of 2-amino-4-hydroxybenzamide and methanesulfonic acid can further improve the conductivity of the electrolyte.
[0040] (3) MXene materials have excellent conductivity and hydrophilicity. Using them as a modifier to treat the surface of graphite felt not only improves the conductivity of graphite felt, but also increases the specific surface area of the graphite felt electrode, thereby providing more reaction interfaces for the reaction of active substances in the electrolyte;
[0041] (4) In the present application, MXene is grafted with ammonium polyphosphate, which can further increase the number of hydrophilic groups on the surface of MXene, making it easier and more firmly adsorbed on the surface of graphite felt. In addition, ammonium polyphosphate can introduce nitrogen and phosphorus sources, and nitrogen and phosphorus doping can be achieved after the modified graphite felt. Nitrogen and phosphorus can form a large number of P-N and P=N bonds on the surface of graphite felt, causing asymmetric spin and charge density changes in the graphite structure, which is VO 2+ or VO2 + It provides abundant adsorption sites, thereby further improving the electrochemical activity of the graphite felt electrode. DETAILED DESCRIPTION
[0042] The present application is further described in detail below with reference to the embodiments.
[0043] The present application provides a rare earth-vanadium liquid flow battery, which is composed of a negative circulation loop, a positive circulation loop, and a diaphragm located between the negative circulation loop and the positive circulation loop;
[0044] The negative circulation loop comprises a negative electrode chamber, a negative electrode electrolyte peristaltic pump, and a negative electrode liquid storage tank, wherein the negative electrode chamber, the negative electrode electrolyte peristaltic pump, and the negative electrode liquid storage tank are sequentially connected by a pipeline, and the negative electrode liquid storage tank is provided with a negative electrode electrolyte, and the negative electrode electrolyte circulates in the negative circulation loop;
[0045] The positive circulation loop comprises a positive electrode chamber, a positive electrode electrolyte peristaltic pump, and a positive electrode liquid storage tank, wherein the positive electrode chamber, the positive electrode electrolyte peristaltic pump, and the positive electrode liquid storage tank are sequentially connected by a pipeline, and a positive electrode electrolyte is provided in the positive electrode liquid storage tank, and the positive electrode electrolyte circulates in the positive circulation loop;
[0046] A negative electrode is arranged in the negative electrode chamber, a positive electrode is arranged in the positive electrode chamber, and the negative electrode chamber and the positive electrode chamber are separated by a diaphragm.
[0047] The working process of the battery is as follows: the negative and positive electrolytes in the negative and positive electrode storage tanks are driven by the electrolyte peristaltic pumps, enter the negative and positive electrode chambers through pipes for electrode reactions, and then flow back to the negative and positive electrode storage tanks. The high-speed flow of the electrolyte is conducive to reducing the electrochemical and concentration polarization in the electrode reaction.
[0048] The charging and discharging process of the battery is as follows: when charging, an external power source is connected, and the electrical energy is converted into chemical energy and stored in the electrolyte; when discharging, an external load is connected, and the chemical energy stored in the electrolyte is converted into electrical energy and used by the load.
[0049] The capacity of the battery stack is determined by the concentration and volume of the electrolyte.
[0050] The 2-amino-4-hydroxybenzamide used in this application has a CAS number of 82049-00-1.
[0051] Examples A1-A7
[0052] Negative electrode electrolyte: Add VSO4 and rare earth oxides into water, stir to dissolve, then add acid solution, stir evenly, finally add stabilizer (obtained by mixing 2-amino-4-hydroxybenzamide and methanesulfonic acid), stir evenly, add water to make the volume to 100 mL, and the negative electrode electrolyte is obtained. The distribution ratio of each component is shown in Table 1.
[0053] Table 1 (Unit: mol / L)
[0054]
[0055] Example A8
[0056] Negative electrode electrolyte: The preparation method is the same as that of Example A1, except that phenol and aniline are used to replace 2-amino-4-hydroxybenzamide, and the molar concentrations of phenol and aniline are both 0.045 mol / L.
[0057] Examples B1-B7
[0058] Positive electrode electrolyte: Add VOSO4 and rare earth oxides into water, stir to dissolve, then add acid solution, stir evenly, finally add stabilizer (obtained by mixing 2-amino-4-hydroxybenzamide and methanesulfonic acid), stir evenly, add water to make the volume to 100 mL, and the negative electrode electrolyte is obtained. The distribution ratio of each component is shown in Table 2.
[0059] Table 2 (Unit: mol / L)
[0060]
[0061] Example B8
[0062] Positive electrode electrolyte: The preparation method is the same as that of Example B1, except that phenol and aniline are used to replace 2-amino-4-hydroxybenzamide, and the molar concentrations of phenol and aniline are both 0.045 mol / L.
[0063] Example C1
[0064] Modified graphite felt: 10 g Ti3AlC2 was mixed with 250 mL of 4 mol / L sodium hydroxide solution, placed in a vacuum ball mill, and subjected to ball milling reaction for 8 h at a ball-to-material ratio of 14:1 and a rotation speed of 1200 rpm. After ball milling, the mixture was vacuum dried at 60 °C to obtain Ti3C2T x powder;
[0065] Ti3C2T x The powder was added into 500 mL of 35 wt.% aqueous solution of ammonium polyphosphate (purchased from McLean, degree of polymerization n < 20, product number A875114), stirred for 16 h in a water bath at 60 °C, and the supernatant was centrifuged to obtain Ti3C2T x Modifiers;
[0066] A 100 mm × 100 mm × 5 mm polyacrylonitrile-based graphite felt was immersed in 250 mL of Ti3C2T x The modified graphite felt was adsorbed at 80°C for 4 hours, washed with deionized water for 3 times after cooling, and freeze-dried. The surface element contents were determined by energy dispersive spectrometer: C 81.55%, O 9.42%, N 2.31%, P 2.46%, and Ti 4.26%.
[0067] Example C2
[0068] Graphite felt: polyacrylonitrile-based graphite felt. Surface element contents measured by energy dispersive spectrometer are: C 99.51%, O 0.49%, N 0%, P 0%, Ti 0%.
[0069] Examples D1-D11, Comparative Examples 1-3
[0070] Rare earth-vanadium liquid flow battery: The graphite felt obtained in Examples C1-C2 was used as the positive and negative electrodes, Nafion 115 proton exchange membrane (purchased from DuPont, USA) was used as the separator, the electrolyte obtained in Examples A1-A7 was used as the negative electrode electrolyte, and the electrolyte obtained in Examples B1-B7 was used as the positive electrode electrolyte. A single cell was assembled, and the electrolyte flow rate was 60 mL / min. The negative electrode electrolyte, positive electrode electrolyte, and positive and negative electrodes used in the batteries in Examples D1-D11 and Comparative Examples 1-3 are shown in Table 3.
[0071] Table 3
[0072]
[0073] Electrochemical performance test:
[0074] The batteries prepared in the examples and comparative examples were subjected to electrochemical performance tests. The test method was as follows: the single cells obtained in the examples and comparative examples were assembled into a battery stack, and the flow rate was uniformly 60 mL / min. On the blue battery test system, the assembled battery stack was tested for 100 constant current charge and discharge cycles, and the test current density was 100 mA / cm 2 The coulombic efficiency and energy efficiency were measured and recorded. The test results are shown in Table 4.
[0075] Table 4
[0076]
[0077] It can be seen from the test results in Table 1 that the rare earth-vanadium liquid flow battery prepared in this application has a current density of 100 mA / cm 2 After 100 cycles of charge and discharge, the coulombic efficiency is 80.6-89.1% and the energy efficiency is 67.9-79.5%. The test results of Examples D1-D11 vary slightly, and the test results are relatively stable and reproducible, indicating that the formula and preparation method of the rare earth-vanadium liquid flow battery of the present application are relatively stable.
[0078] Compared with Example D1:
[0079] The negative electrode electrolyte of Comparative Example 1 adopts A7, that is, 2-amino-4-hydroxybenzamide is not added to the negative electrode liquid. The test results of the battery stack are: coulomb efficiency 54.5%, energy efficiency 45.0%, and the electrochemical performance decreases significantly.
[0080] The positive electrode liquid of Comparative Example 2 uses B7, that is, 2-amino-4-hydroxybenzamide is not added to the positive electrode electrolyte. The test results of the battery stack are: coulomb efficiency 48.1%, energy efficiency 35.9%, and the electrochemical performance decreases more. This may be because 2-amino-4-hydroxybenzamide can not only improve the conductivity of the electrolyte, but also adsorb vanadium ions due to the presence of hydroxyl and amino groups, effectively organizing V 5+ precipitation, thereby improving the stability of the positive electrode electrolyte and enhancing the cycle charge and discharge performance.
[0081] The positive and negative electrodes of Comparative Example 3 use C2, that is, the positive and negative electrodes use unmodified polyacrylonitrile-based graphite felt. The test results of the battery stack are: coulombic efficiency 74.6%, energy efficiency 62.4%, compared with the modified graphite felt used in Example 1, it shows relatively low coulombic efficiency and energy efficiency, indicating that the electrochemical activity of the electrode and the electrochemical performance of the battery stack can be greatly improved by grafting MXene with ammonium polyphosphate and then modifying the graphite felt.
[0082] The negative electrode electrolyte of Comparative Example 4 adopts A8, that is, the negative electrode electrolyte adopts phenol and aniline instead of 2-amino-4-hydroxybenzamide, and the obtained stack test results are: coulomb efficiency 62.7%, energy efficiency 56.1%, and the electrochemical performance decreases significantly.
[0083] The positive electrode liquid of Comparative Example 5 adopts B8, that is, phenol and aniline are used in the positive electrode electrolyte instead of 2-amino-4-hydroxybenzamide. The test results of the battery stack are: coulomb efficiency 55.2%, energy efficiency 45.6%, and the electrochemical performance is significantly reduced. This is because 2-amino-4-hydroxybenzamide contains amino groups, hydroxyl groups and amide groups at the same time, all of which have a high chelating adsorption effect of vanadium ions. In the presence of methanesulfonic acid, the chelating adsorption effect is more prominent, which effectively prevents the precipitation of V5+, thereby improving the stability of the positive electrode electrolyte and improving the cycle charge and discharge performance.
[0084] The above is only the preferred implementation of the present application. The protection scope of the present application is not limited to the above embodiments. All technical solutions under the concept of the present application belong to the protection scope of the present application. It should be pointed out that for ordinary technicians in this technical field, some improvements and modifications without departing from the principle of the present application should also be regarded as the protection scope of the present application.
Claims
1. A rare earth-vanadium liquid flow battery, characterized in that: It consists of a negative circulation loop, a positive circulation loop, and a diaphragm located between the negative circulation loop and the positive circulation loop; The negative circulation loop comprises a negative electrode chamber, a negative electrode electrolyte peristaltic pump, and a negative electrode liquid storage tank, wherein the negative electrode chamber, the negative electrode electrolyte peristaltic pump, and the negative electrode liquid storage tank are sequentially connected by a pipeline, and the negative electrode liquid storage tank is provided with a negative electrode electrolyte, and the negative electrode electrolyte circulates in the negative circulation loop; The positive circulation loop comprises a positive electrode chamber, a positive electrode electrolyte peristaltic pump, and a positive electrode liquid storage tank, wherein the positive electrode chamber, the positive electrode electrolyte peristaltic pump, and the positive electrode liquid storage tank are sequentially connected by a pipeline, and a positive electrode electrolyte is provided in the positive electrode liquid storage tank, and the positive electrode electrolyte circulates in the positive circulation loop; A negative electrode is arranged in the negative electrode chamber, a positive electrode is arranged in the positive electrode chamber, and the negative electrode chamber and the positive electrode chamber are separated by a diaphragm; The negative electrode electrolyte is composed of V 2+ / V 3+ , rare earth ions, acid solution and stabilizer; The positive electrode electrolyte is composed of VO2 + / VO 2+ , rare earth ions, acid solution and stabilizer; The stabilizer consists of 2-amino-4-hydroxybenzamide and methanesulfonic acid.
2. The rare earth-vanadium redox flow battery according to claim 1, characterized in that: The concentration of the stabilizer is 0.01-0.3 mol / L.
3. The rare earth-vanadium redox flow battery according to claim 1, characterized in that: The molar ratio of the 2-amino-4-hydroxybenzamide to the methanesulfonic acid is 1:(0.01-0.2).
4. The rare earth-vanadium redox flow battery according to claim 1, characterized in that: The concentration of the rare earth ions is 0.01-3 mol / L, and the rare earth is selected from at least one of scandium, yttrium, lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium and lutetium.
5. The rare earth-vanadium redox flow battery according to claim 1, characterized in that: The acid solution has a concentration of 1-6 mol / L, and the acid solution is selected from at least one of hydrochloric acid, sulfuric acid, acetic acid, and trifluoroacetic acid.
6. The rare earth-vanadium redox flow battery according to claim 1, characterized in that: The V 2+ / V 3+ The concentration is 0.01-10 mol / L, the VO2 + / VO 2+ The concentration is 0.01-10mol / L.
7. The rare earth-vanadium redox flow battery according to claim 1, characterized in that: The positive electrode and the negative electrode are selected from at least one of graphite felt, modified graphite felt, carbon felt and carbon cloth.
8. The rare earth-vanadium redox flow battery according to claim 7, characterized in that: The positive electrode and the negative electrode adopt modified graphite felt, and the modified graphite felt is prepared by the following preparation method: The MAX phase compound is etched with a sodium hydroxide solution, and MXene powder is obtained after drying. The MXene powder is placed in an ammonium polyphosphate aqueous solution, stirred and mixed, and the upper clear liquid is taken by centrifugation to obtain a MXene modifier; graphite felt is placed in the MXene modifier, heated for reaction, and the graphite felt is washed after the reaction is completed, and the modified graphite felt is obtained after drying.
9. The rare earth-vanadium redox flow battery according to claim 8, characterized in that: The concentration of the sodium hydroxide solution is 2-10 mol / L, and the mass fraction of the ammonium polyphosphate aqueous solution is 30-60 wt.%.
10. The rare earth-vanadium redox flow battery according to claim 1, characterized in that: The preparation method of the negative electrode electrolyte comprises the following steps: 2+ / V 3+ Add the compound and the compound containing rare earth ions into water, stir to dissolve, then add acid solution, stir evenly, finally add stabilizer, stir evenly, add water to adjust the concentration of each component, and obtain; The preparation method of the positive electrode electrolyte comprises the following steps: + / VO 2+ The compound and the compound containing rare earth ions are added to water, stirred to dissolve, then the acid solution is added, stirred evenly, and finally the stabilizer is added, stirred evenly, and water is added to adjust the concentration of each component to obtain the product.
Citation Information
Patent Citations
All-vanadium battery electrolyte and preparation method thereof
CN106340664A
Method for modifying electrode for organic flow battery, the electrode, the battery and energy storage system
CN110492055A
Vanadium redox flow battery, electrolyte of vanadium redox flow battery and method for improving energy density of electrolyte
CN116344887A
High-temperature-resistant electrolyte as well as preparation method and application thereof
CN117747897A